Utilizzo del test di attivazione dei basofili (BAT) per la diagnosi di reazione allergica a piperacillina in ambito professionale: descrizione di un caso clinico/A clinical case of occupational allergy to piperacilline. A novel diagnostic method... - Marraccini, Paolo; Digiesi, Giuseppe; Pignatti, Patrizia; Bordini, Lorenzo; Previdi, Mario (La Medicina del Lavoro, 2013)
Summary «A clinical case of occupational allergy to piperacilline. A novel diagnostic method: Basophil Activation Test (BAT)». Background: Piperacillin, unlike other antibiotics, rarely causes immediate allergic reactions. Only two cases related to occupational exposure are reported in the literature. Objectives: Adoption of new methods for diagnosis of occupational allergy to drugs. Methods: An atopic nurse, aged 30 years, was referred to our hospital for an allergic work-related reaction to piperacillin. The patient had suffered two successive episodes with immediate cutaneous reaction, angioedema and dyspnoea after preparing piperacillin. Almost four years previously she had suffered from similar symptoms after taking amoxicillin. She was submitted to a clinical examination and a routine allergic test, performing also specific IgE (Phadia Pharmacia ImmunoCap) and BAT (Basophil Activation Test) for Beta-lactam antibiotics. Results: A positive response to piperacillin was observed in our case using BAT, a new non- invasive and safe method, that proved useful for diagnosis of allergy. Moreover, we observed a change from an allergic reaction for therapeutic use of amoxicillin to a work-related adverse reaction to another beta-lactam, piperacillin. Conclusions: In previous clinical cases cutaneous and specific challenge tests were performed for diagnosis. At present, availability of an in vitro test, such as BAT, may provide new diagnostic opportunities, and a useful tool for studying clinical cases other than, in perspective, monitoring exposed workers. Preventive measures were taken in the workplace to lower the risk of sensitization and allergic response. The nurse was transferred to a well controlled job. Riassunto Introduzione: La piperacillina, a differenza di altri antibiotici, raramente induce reazioni allergiche di tipo immediato. Obiettivi: Adozione in ambito occupazionale di nuovi criteri diagnostici che si utilizzano per le farmaco allergie. Metodi: Viene riportato il caso clinico di un’infermiera professionale, atopica, giunta alla nostra attenzione per due episodi, occorsi a breve distanza, caratterizzati da manifestazioni cutanee pomfoidi, angioedema e difficoltà respiratoria dopo la preparazione in ambito lavorativo di un antibiotico, la piperacillina. In precedenza la paziente aveva lamentato manifestazioni analoghe dopo assunzione di amoxicillina per via orale a scopo terapeutico. La valutazione delle IgE specifiche per beta-lattamici ha dato esito negativo. E’ stato eseguito il BAT (Test di Attivazione dei Basofili), non invasivo, oggi ampiamente utilizzato per la diagnosi di forme IgE mediate, fra cui quelle da farmaci, che ha dato esito positivo per la piperacillina. Risultati: Il BAT ha confermato il suo ruolo crescente nella diagnosi non invasiva delle reazioni avverse a farmaci. Conclusioni: La particolarità del caso sta nel fatto che da una reazione tradizionale terapeutica ad antibiotici si è avuta l’evoluzione in una forma professionale, e che è stata adottata una nuova e promettente metodica diagnostica, che evita le possibili reazioni in vivo con gli strumenti diagnostici tradizionali. Alla diagnosi hanno fatto seguito misure di prevenzione e protezione sul luogo di lavoro finalizzate a ridurre il rischio di sensibilizzazione e di reazioni allergiche.